OCCURRENCE DATA OF THE NEOTROPICAL OTTER Lontra longicaudis Olfers, 1818 IN THE MANU BIOSPHERE RESERVE - COLAN-RODRIGUEZ, Renato Walter (2023)
Lontra longicaudis Olfers, 1818 is a widely distributed species in North, Central and South America. They are categorized as Near Threatened by the IUCN, but they are not under legal protection in Peru, where their documentation has been limited. Here we present occurrence data of this species inside the Manu Learning Centre biological station, in the Manu Biosphere Reserve from the period 2012 – 2022, and a suggestion about how to assess this species in the future, using already existing legal regulations.